Isolation of a Novel Bacterial Strain Capable of Producing Abundant Extracellular Membrane Vesicles Carrying a Single Major Cargo Protein and Analysis of Its Transport Mechanism - Chen, Chen; Kawamoto, Jun; Kawai, Soichiro; Tame, Akihiro; Kato, Chiaki; Imai, Tomoya; Kurihara, Tatsuo (Frontiers in Microbiology, 2020)
Extracellular membrane vesicles (EMVs) play an important role in various bacterial activities. EMVs have potential for use as vaccines, drug-delivery vehicles, platforms for extracellular production of recombinant proteins, and so on. In this study, we newly isolated a cold-adapted bacterium, Shewanella vesiculosa HM13, which abundantly produces EMVs, characterized them, and analyzed their cargo transport mechanism. S. vesiculosa HM13, isolated from the intestine of a horse mackerel as a prospective host for a low-temperature secretory protein expression system, produced a single major secretory protein, P49, of unknown function in the culture supernatant. Analysis using sucrose density gradient ultracentrifugation indicated that P49 is a cargo protein carried by EMVs. S. vesiculosa HM13 displayed extensive blebbing on the surface of the outer membrane, and the size of blebs was comparable to that of EMVs. These blebs are thought to be precursors of the EMVs. Disruption of the P49 gene resulted in only a marginal decrease in the EMV production, indicating that the EMVs are produced even in the absence of the major cargo protein. Whole genome sequencing of S. vesiculosa HM13 revealed that this bacterium has a gene cluster coding for a non-canonical type II protein secretion system (T2SS) homolog in addition to a gene cluster coding for canonical T2SS. The P49 gene was located downstream of the former gene cluster. To examine the role of the putative non-canonical T2SS-like translocon, we disrupted the gene coding for a putative outer membrane channel of the translocon, named GspD2. The gspD2 disruption lead to disappearance of P49 in the EMV fraction, whereas the production of EMVs was not significantly affected by this mutation. These results are indicative that the T2SS-like machinery functions as a novel type of protein translocon responsible for selective cargo loading to the EMVs. We also found that GFP fused to the C-terminus of P49 expressed in S. vesiculosa HM13 was transported to EMVs, indicating that P49 is useful as a carrier to deliver the fusion partner to EMVs. These findings deepen our understanding of the mechanism of biogenesis of EMVs and facilitate their applications.